2020
DOI: 10.14440/jbm.2020.327
|View full text |Cite
|
Sign up to set email alerts
|

A 2D and 3D melanogenesis model with human primary cells induced by tyrosine

Abstract: Research on melanogenesis, its regulation in health and disease, and the discovery of new molecules with pigmenting and depigmenting activities use different models. Here we standardize a protocol based on previous ones using primary human melanocytes and keratinocytes in co-cultures, in which melanogenesis was induced under mild conditions by the addition of tyrosine plus ammonium chloride (NH4Cl). The expression of MITF, TYR, TYRP1, and Melan-A as well as melanin content were measured. Furthermore, we extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Pigmentation in cocultures in the absence of an external stimulus is prolonged and can take >10 d [84]; external factors such as UVB irradiation or α-MSH are necessary to stimulate melanogenesis and melanosome transfer in HEMn-DP cocultures [85], although HEMn-DP cells are unresponsive to α-MSH-stimulation in monocultures [86]. Moreover, a recent study demonstrated that a mild stimulus involving a combination of l-tyrosine and NH 4 Cl stimulated pigmentation in HEMn-DP cocultures within a short duration of 5 d [87]. Further studies employing the use of such coculture methods with external stimulators to validate whether CMT-308 could in fact suppress the transfer of melanosome in recipient keratinocytes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation in cocultures in the absence of an external stimulus is prolonged and can take >10 d [84]; external factors such as UVB irradiation or α-MSH are necessary to stimulate melanogenesis and melanosome transfer in HEMn-DP cocultures [85], although HEMn-DP cells are unresponsive to α-MSH-stimulation in monocultures [86]. Moreover, a recent study demonstrated that a mild stimulus involving a combination of l-tyrosine and NH 4 Cl stimulated pigmentation in HEMn-DP cocultures within a short duration of 5 d [87]. Further studies employing the use of such coculture methods with external stimulators to validate whether CMT-308 could in fact suppress the transfer of melanosome in recipient keratinocytes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For co‐cultures, keratinocytes (2.5 × 10 5 ) were seeded in medium KBM Gold supplemented with KBM Gold Single Quots, plated on 100 mm Petri plates (Corning ® ) for 24 h; then, melanocytes (2.5 × 10 5 ) were added in 10 ml of the same medium. Pigmentation was induced with tyrosine (0.25 mM) and ammonium chloride (5 mM) after 24 h 21 . Unless otherwise stated, co‐cultures were incubated for 5 days at 37°C in a humidified incubator with a 5% CO 2 atmosphere without further handling.…”
Section: Experimental Designmentioning
confidence: 99%
“…After 2 h, keratinocytes (2.5 × 10 5 ) and melanocytes (1.7 × 10 5 ) were seeded on the top of each construct in RAFT: KGM‐Gold Bullet Kit Medium (1:1). After 24 h, the construct was transferred and maintained at an air‐liquid interface for 10 days in a 5% CO 2 incubator with low humidity, and the medium supplemented with tyrosine (0.25 mM) + NH 4 Cl (5 mM) was replaced every 2 days 21 . After stratification, skins were fixed in 10% buffered formalin at 4°C for 12 h, followed by dehydration in solutions containing increasing concentrations of alcohol and xylene for paraffin inclusion.…”
Section: Experimental Designmentioning
confidence: 99%